Translational or translationable? A call for ethno-immersion in (empirical) bioethics research - Parsons, Jordan A. (Bioethics, 2024)
The shift towards 'empirical bioethics' was largely triggered by a recognition that stakeholders' views and experiences are vital in ethical analysis where one hopes to produce practicable recommendations. Such perspectives can provide a rich resource in bioethics scholarship, perhaps challenging the researcher's perspective. However, overreliance on a picture painted by a group of research participants—or on pre-existing literature in that field—can lead to a biased view of a given context, as the subjectivity of data generated in these ways cannot (and should not wholly) be escaped. In response, we propose the implementation of a complementary approach of ethno-immersion in bioethics research. By positioning oneself in the context being researched, the researcher can better understand the realities of that context. The researcher's understanding will, naturally, be subjective too. However, it will act as a better developed and more informed outsider view, when considering the picture painted by participants and previous studies, thus enabling the researcher to introduce more nuance when analysing data. We introduce this approach after examining what we call the context detachment problem, whereby some bioethics scholarship—empirical or otherwise—fails to reflect the reality of the healthcare setting it concerns. Our proposed ethno-immersion (which differs from formal ethnography) is then explored as a response, highlighting its benefits, and answering the question of timing within a research project. Finally, we reflect on the applicability of our proposal to non-empirical bioethics scholarship, concluding that it remains important but may require some adjustments.